CORAK ILMI DALAM TAFSIR KEMENAG (EDISI YANG DISEMPURNAKAN) - Azizy, Jauhar; Syarifuddin, M. Anwar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
The development of science and technology has led to the emergence of patterns of scientific (laun ‘ilmi) interpretation as a new mode of interpretation of the Qur’an. Scientific pattern is in line with the development of a more rational method of interpretation (tafsir bi al - ra'yi). The existence of a scientific pattern is very important to be able to measure the close relationship between Islam and the development of science. One trigger of scientific pattern is the dialectic between Western and Muslim scholars . This paper will attempt to show the scientific interpretation in Al-Qur’an and Tafsirnya (Edisi Yang Disempurnakan), Ministry of Religious Affairs, 2004 and how the scientific pattern was formed in its interpretation. The results of this article argues that Al-Qur’an dan Tafsirnya (Edisi yang Disempurnakan), Ministry of Religious Affairs, 2004 very respond to the development of science in its interpretation. It is not only some of Interpration Team is an alumni of the University of Al-Azhar, Egypt, which is influenced by the thought of Muhammad Abduh, but also involves scientists from the Indonesian Institute of Sciences (LIPI) when interpreting the verses of the Qur'an that contain scientific cues. It is not contrary to the spirit of the Qur'an that encourage the growth and advancement of the development of science and technology.